Characterization of La-promoted Ni/Al2 O3 catalysts for hydrogen production from glycerol dry reforming - Siew, Kah Weng; Lee, Hua Chyn; Jolius, Gimbun; Cheng, C. K. (Elsevier, 2014)
In the current paper, dry (CO2)-reforming of glycerol, a new reforming route, was carried out over alumina (Al2O3)-supported, non-promoted and lanthanum-promoted nickel (Ni) catalysts. Both sets of catalysts were synthesized via a wet co-impregnation procedure. Physicochemical characterization of the catalysts showed that the promoted catalyst possessed smaller metal crystallite size, hence higher metal dispersion compared to the virgin Ni/Al2O3 catalyst. This was also corroborated by the surface images captured by the FESEM analysis. From temperature-programmed calcination analysis, the derivative weight profiles revealed two peaks, which represent a water elimination peak at a temperature range of 373 to 473 K followed by nickel nitrate decomposition from 473 to 573 K. In addition, BET surface area measurements gave 85.0 m2·g−1 for the non-promoted Ni catalyst, whilst the promoted catalysts showed an average of 1% to 6% improvement depending on the La loadings. Significantly, reaction studies at 873 K showed that glycerol dry reforming successfully produced H2. The 2%La-Ni/Al2O3 catalyst, which possessed the largest BET surface area, gave an optimum H2 generation (9.70%) at a glycerol conversion of 24.5%.